Urgensi Pembelajaran Inkuiri di Abad ke 21: Kajian Literatur - Devi Septiani; Susanti Susanti (SAP (Susunan Artikel Pendidikan), 2021)
The challenges of the 21st century have become important in education. The 21st century turns life into four pillars, namely learning to know, learning to do, learning to be, and learning to live together. The four pillars contain specific skills that need to be developed in learning activities, such as critical thinking, communicating, collaborating, innovation and creation, information literacy, and problem solving. This study examines the importance of the role of inquiry learning as an alternative learning that can solve the challenges of the 21st century. Experts agree that the answer to the challenges of the 21st century can be concluded by ensuring that students have scientific process skills. Overall skills can be taught in student-centered learning. The results of the mapping are sourced from 40 research articles related to the inquiry. The analysis shows that inquiry is a learning model that can be used to guide students to achieve all skills. An inquiry is a learning that can teach with various stages within one inquiry cycle. The phases may be different for each cycle, however, it still boils down to an agreement that the point of inquiry is in the investigation. An inquiry makes students have free space to learn, but it provides clear exploration limits.